ANALISIS PENGARUH SISTEM PENGENDALIAN INTERN DAN IMPLEMENTASI SISTEM AKUNTANSI KEUANGAN DAERAH (SAKD) TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI EMPIRIS PADA SKPD KOTA MANADO) - Lumintang, Gyshella Smylie; Lambey, Linda; Tangkuman, Steven (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Local government financial statement made to provide information about financial position and all transactions conducted by local government. A qualified local government financial statement must have relevant, reliable, comparable and understandable characteristics. There are several factors that may affect the quality of local government financial statements, that is, internal control system and financial accounting system of local government. This research was aimed to determine the effect of internal control system and financial accounting system of local government to the quality of financial statements at the local government of Manado City. Respondents of this research were 40 financial management personnel from 10 Manado City SKPD from 168 population of financial management personnel of Manado City SKPD. This research used a quantitative approach, using primary data through questionnaires. The variables in this research is the internal control system and financial accounting system of local government as the independent variables and the quality of local government financial statement as the dependent variable. The data collected were processed using SPSS version 23.0. The statistical methods used to test the hypotheses is multiple linear regression analysis. The results of hypothesis shown that the internal control system has a significant positive effect on the quality of Manado City local government financial statementÂ  while the implementation of financial accounting system of local government has no significant positive effect on the quality of Manado City local government financial statements and internal control system and financial accounting system of local government has a significant positive effect on the quality of Manado City local government financial statement.Keywords : Internal control system, financial accounting system of local government, financial accounting system of local government